Gastritis crónica con Helicobacter Pylori positivo como factor de riesgo de Metaplasia intestinal completa e incompleta - Alayo Jave, Roberto Carlos (2010)
In order to determine the association of chronic gastritis with Helicobacter pylori positive with complete and incomplete intestinal metaplasia; the present study was carried out of cases and controls, in the pathology department of the Belén Hospital of Trujillo during the years 2007 and 2008. Firstly, the histological sheet of each case was reviewed colored with hematoxylin eosin staining, in order to confirm the presence or not of Helicobacter pylori as well as complete and incomplete intestinal metaplasia. The study performed in 156 patients, 52 cases with chronic metaplastic gastritis and 104 (52 + 104 = 156) controls with non-metaplastic chronic gastritis. The chi-square comparison test was used with a level of significance of 5% and statistically association was found meaningful. Therefore, we conclude that there is a statistically significant association between gastritis chronic with helicobacter pylori positive and the presence of intestinal metaplasia, whether this Complete or incomplete in the gastric mucosa